Health shock and preference instability: Assessing health-state dependency of willingness-to-pay for corrective eyeglasses - Islam, Muhammed Nazmul; Rabbani, Atonu; Sarker, Malabika (BMC, 2022)
This article was published in BMC Health Economics Review [ © The Author(s). 2019 Open Access This article is distributed under the terms of the Creative Commons Attribution 4.0 International License (http://creativecommons.org/licenses/by/4.0/)] and the definite version is available at: https://doi.org/10.1186/s13561-019-0249-3 The Journal's website is at: https://healtheconomicsreview.biomedcentral.com/articles/10.1186/s13561-019-0249-3#citeas